Reacting Quickly and Protecting Jobs: The Short-Term Impacts of the COVID-19 Lockdown on the Greek Labor Market - Gordon Betcherman; Nicholas Giannakopoulos; Ioannis Laliotis; Ioanna Pantelaiou; Mauro Testaverde; Giannis Tzimas (Institute of Labor Economics (IZA), 2020)
We use administrative, survey, and online vacancy data to analyze the short-term labor market impacts of the COVID-19 lockdown in Greece. We find that flows into unemployment have not increased; in fact, separations were lower than would have been expected given trends in recent years. At the same time, employment was about 12 percent lower at the end of June than it would have been without the pandemic. Our interrupted time series and difference-in-differences estimates indicate that this was due to a dramatic slowdown in hiring during months when job creation typically peaks in normal years, mostly in tourism. While we do not formally test the reasons for these patterns, our analysis suggests that the measures introduced to mitigate the effects of the crisis in Greece have played an important role. These measures prohibited layoffs in industries affected by the crisis and tied the major form of income support to the maintenance of employment relationships.
Keywords: J21; J60; J68; 330; Greece; COVID-19; pandemic; labor market impacts